Enhanced anaerobic fermentation of dairy manure by microelectrolysis in electric and magnetic fields. (February 2020) - Qu, Guangfei; Lv, Pei; Cai, Yingying; Tu, Can; Ma, Xi; Ning, Ping
Abstract: The degradation rate of lignocellulose and methane (CH4 ) content must be improved through anaerobic fermentation process engineering in order to promote the proper operation of anaerobic organic waste removal without secondary pollution and low cost. The present study investigates mesophilic anaerobic fermentation of dairy manure (DM) under weak magnetic and low operation voltage (0.3–0.8 V). The results showed that the effect of electric and magnetic fields (EMF) can significantly enhance the fermentation, and improve the CH4 content of biogas and accelerate the degradation rate of lignocellulose. Fe-C microelectrolysis intensified the anaerobic fermentation of DM, the highest CH4 content was 87%, the cellulose degradation rate was 36%, increased by 125%, and the lignin degradation rate was 23%, increased by 203%, under loading 0.5 V voltage and weak magnetic field. Metagenome sequence results showed that EMF and Fe-C microelectrolysis can not only promote the microbial diversity, but also increase the abundance of functional microorganisms at various stages. This finding provides theoretical support and foundation for the extraordinary efficiency degradation of lignocellulose and the electric and magnetic regulation of anaerobic fermentation microorganism system. Highlights: Methane production and methane content increased significantly in EMF. The lignin degradation rate was 23%, increased by 203%. Effective microorganisms in all fermentation stages can be enhanced in EMF.